The Relationship between Internet Gaming Addiction and Attention Deficit Hyperactivity Disorder’s Symptoms in Young Adults - Umara Rauf; Mahnoor Zahid; Haddiqa Rizvi; Hurmat Shakeel (Journal of Pakistan Psychiatric Society, 2026)
OBJECTIVEThe aim of this study is to explore the relationship between video gaming addiction and Attention Deficit Hyperactivity Disorder (ADHD) symptoms among young adults. STUDY DESIGN A correlational cross-sectional quantitative research design was used.PLACE AND DURATION OF STUDY This study was conducted at different universities of Sialkot, Pakistan from February, 2024 to July, 2024.METHODA purposive sample of 200 young adults with internet gaming addiction was taken. A self-developed demographic sheet was administered along with the Internet Gaming Disorder Scale Short-Form (Pontes, & Griffiths, 2015) to measure internet gaming addiction. Attention deficit/ hyperactivity disorder’s symptoms were measured using Adult ADHD Self-Report Scale (ASRS-v1.1 Symptom Checklist) (Kessler, et al., 2005). For the analysis of data, descriptive statistics, Pearson Product Moment Correlation Coefficient and regression were applied using SPSS v25.0 software.RESULTS Study found a significant positive relationship between IGD (Internet Gaming Disorder Scale) score and ADHD (Attention deficit/ hyperactivity disorder) symptoms in young adults.CONCLUSIONThis research highlights the comorbidity of psychopathology such as ADHD, in video gaming addicts, suggesting that individuals with higher internet gaming addiction are more likely to exhibit signs of ADHD symptoms.